Cochrane Database of Systematic Reviews 2012
DOI: 10.1002/14651858.cd001175.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Computer-generated reminders delivered on paper to healthcare professionals; effects on professional practice and health care outcomes

Abstract: Background Clinical practice does not always reflect best practice and evidence, partly because of unconscious acts of omission, information overload, or inaccessible information. Reminders may help clinicians overcome these problems by prompting them to recall information that they already know or would be expected to know and by providing information or guidance in a more accessible and relevant format, at a particularly appropriate time. This is an update of a previously published review. Objectives To eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(80 citation statements)
references
References 344 publications
3
76
0
1
Order By: Relevance
“…Implementing reminders alone improved care by 11.2% (IQR, 6.5-19.6%); implementing reminders in addition to another intervention led to improved rates of 4% (IQR, 3-6%). 37 Providing an explanation of the content on the reminder seemed to improve the effect (median, 12.0% for explanation vs 4.2% for no explanation). 37 Our reminders provided a concise explanation of the need for CRC screening in asymptomatic individuals.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Implementing reminders alone improved care by 11.2% (IQR, 6.5-19.6%); implementing reminders in addition to another intervention led to improved rates of 4% (IQR, 3-6%). 37 Providing an explanation of the content on the reminder seemed to improve the effect (median, 12.0% for explanation vs 4.2% for no explanation). 37 Our reminders provided a concise explanation of the need for CRC screening in asymptomatic individuals.…”
Section: Discussionmentioning
confidence: 97%
“…35 Two recent Cochrane reviews of physician chart reminders have shown minimal to moderate effects. 36,37 Computer reminders achieved an improvement of 3.8% (interquartile range [IQR], 0.4 -16.3%) for ordering tests. 36 Our chart reminder increased colonoscopy testing by 5.9% over usual care (not significant), which is similar to the median improvement in the review by Shojania et al, 36 but did not improve overall rates of CRC screening.…”
Section: Discussionmentioning
confidence: 99%
“…The wider use of electronic health care systems and health records may lead to improved adherence to clinical guidance due to automation. Certainly computer-generated reminders appear to improve adherence to protocols [23]. A number of guidelines also provide clinical decision support systems, usually in the form of software programs, to assist with uptake and implementation.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, mobile health (mHealth) technologies might be used to ease the access of health programs to a large number of individuals at relatively low-cost [10,11]. When integrated to clinical decision support systems (CDSS), what provide recommendations and assists in clinical decision-making at the point of care, mHealth technologies might increase the accuracy in diagnosis and treatment, in an effort to improve quality of care [9].…”
Section: Introductionmentioning
confidence: 99%